Peran Sport Entrepreneurship Dalam Mendorong Pertumbuhan Industri Olahraga Dan Ekonomi Kreatif Di Era Digital - Nur Kholilah Harahap; Albert Guido Simanjuntak (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the role of sports entrepreneurship in driving the growth of the sports industry and the creative economy in the digital age. The method used in this study is a literature review, examining various national and international journals relevant to the research topic. The findings indicate that sports entrepreneurship plays a crucial role in creating business opportunities, fostering innovation, and driving the development of the sports industry. Additionally, sports entrepreneurship contributes to the creative economy through the development of creativity-based products and services, such as digital sports content, apparel design, and the organization of innovative sports events. Advances in digital technology further reinforce this role by streamlining marketing, expanding market reach, and creating new digital-based business models. However, there are several challenges faced, such as limited capital, a lack of managerial skills, and low technology adoption by entrepreneurs. Therefore, efforts to enhance competencies, foster innovation, and secure support from various stakeholders are necessary so that sports entrepreneurship can develop optimally and make a tangible contribution to the economy.